The Effect of Horizontal Tooth Brushing Methods to The Surface Roughness of NCR, GIC, and RMGIC in Class V Cavities - Arba, Khairunnisa Fadhilatul; Aju Fatmawati, Dwi Warna; Lestari, Sri (Journal of Indonesian Dental Association, 2021)
Introduction: Class V cavity can occur due to horizontal tooth brushing methods. Horizontal brushing and abrasive materials on toothpaste allegedly cause surface roughness in the restorative material. Surface roughness causes the retention of plaque and discoloration that will ultimately affect the aesthetic and durability of the restoration. Glass ionomer cement (GIC), resin-modified glass ionomer cement (RMGIC), and nanofiller composite resin (NCR) are aesthetic restorative materials usually applied to restore the the class V cavity. Objective: To determine the surface roughness of Glass ionomer cement (GIC), resin-modified glass ionomer cement (RMGIC), and nanofiller composite resin (NCR) after brushing with horizontal methods. Methods: This study used a pre and post test control group design. There were three groups, each consisted of 6 samples of bovine’s teeth that was class V prepared and restored. Group 1 NCR, group 2 GIC, and group 3 RMGIC. Each group was brushed with horizontal methods as many as 5,110 movements. The measurements of surface roughness were taken before and after the samples were brushed with surface roughnes tester. Data were statistically analyzed using one way Anova. Result: There were an increase in the surface roughness of each group after brushing. The result showed that the value of surface roughness are as follows GIC > RMGIC > NCR. There were also significant differences among the value of surface roughness in each group. Conclusion: The smallest increase of surface roughness after brushing shows that of nanofiller composite resin, followed by resin-modified glass ionomer cement, and glass ionomer cement.